Core obligations : building a framework for economic, social and cultural rights - Chapman, Audrey R.; Russell, Sage.; American Association for the Advancement of Science; HURIDOCS (Network) (Antwerp ; New York : Intersentia ; Ardsley, N.Y. : Transnational Pub. [distributor for North America], 2002)
"[S]eries of papers on the rights enumerated in the International Covenant on Economic, Social, and Cultural Rights, written ... at the request of the American Association for the Advancement of Science (AAAS) and Human Rights Information and Documentation Systems, International (HURIDOCS)"--Page xv.
Introduction -- The right to work: core minimum obligations -- Minimum oligations with respect to Article 8 of the International Covenant on Economic, Social and Cultural Rights -- The right to social security in the International Covenant on Economic, Social and Cultural Rights -- Family rights and the United Nations Covenant on Economic, Social and Cultural Rights: Article 10(1) -- The minimum core obligations of states under Article 10(3) of the International Covenant on Economic, Social and Cultural Rights -- The right to adequate food: violations related to its minimum core content -- Core obligations related to the right to health -- In search of the core content of the right to education -- Scientists' rights and the human right to the benefits of science -- The right to take part in cultural life: toward defining minimum core obligations related to Article 15(1)(A) of the International Covenant on Economic, Social and Cultural Rights -- Core obligations related to ICESCR Article 15(1)(C) -- International Covenant on Economic Social and Cultural Rights -- Maastricht Guidelines on Violations of Economic, Social and Cultural Rights.
"Series of papers on the rights enumerated in the International Covenant on Economic, Social, and Cultural Rights, written ... at the request of the American Association for the Advancement of Science (AAAS) and Human Rights Information and Documentation Systems, International (HURIDOCS)"--Page xv.
Text of the Covenant: p. 333-341.
Includes bibliographical references.
Keywords: International Covenant on Economic, Social, and Cultural Rights -- (1966 December 16); Pacte international relatif aux droits economiques, sociaux et culturels -- (1966); International Covenant on Economic, Social, and Cultural Rights (1966 December 16); Human rights; Droits de l'homme.; Droits de l'homme (Droit international); Droits economiques et sociaux; Droits de l'homme.; Conventions internationales; Responsabilite de l'Etat.; Application des lois; Droits fondamentaux; Human rights